Best Answer

We can simplify this expression by combining the like terms. Here the likes terms are the z's and the x's.

2z + 3z + 5z = 10z. (If we have 2 of something and add three of the same thing and then 5 of the same thing we will end up with 10 of that thing).

Likewise we can combine the x's.

6x - 2x = 4x. (You could think of this as 6x + - 2x if this helps with the idea of "combining".)

Therefore we are able to simplify this expression as:

2z + 3z + 5z + 4 + 6x - 2x = 10z + 4 + 4x.

Q: What is the answer for adding polynomials 2z plus 3z plus 5z plus 4 plus 6x-2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-2z + 3

3z + 8 + 2z + 6 = 5z + 14

4z + 3 = 6 + 2zSubtract 2z from each side of the equation:2z + 3 = 6Subtract 3 from each side:2z = 3Divide each side by 2:z = 3/2 = 1.5

60j + 2z = 6

2z+17=21 subtract 17 from both sides. 2z=4 divide both sides by 2 z=2

Related questions

-2z + 3

3z + 8 + 2z + 6 = 5z + 14

2z+9.75-7z=-5.15

4z + 3 = 6 + 2zSubtract 2z from each side of the equation:2z + 3 = 6Subtract 3 from each side:2z = 3Divide each side by 2:z = 3/2 = 1.5

2z

60j + 2z = 6

63

2z+17=21 subtract 17 from both sides. 2z=4 divide both sides by 2 z=2

Y. .....2z.....

The answer to 2Z plus 9.75 subtract 7Z subtract equals 14.90. This is a math problem.

3y+2z

12+1z